Identification of the Suitability of Sea Cucumber Cultivation Locations on Saugi Island Using GIS Based on Physical and Chemical Parameters - Rasul, Mat; Ramadhan, Faridun; Nurhaya, Nurhaya; Faizin, Syuura Annisa; Rahman, FathuL; Muslimah, Muslimah; Al-Adawiyah, Rabi'ah; Adam, Adam; Sunandar, Ikbal; Ibrahim, Siti Fadillah; Rahman, Ahmad Zaky; Baci, Muhammad Ihsan (JURNAL AKUAKULTURA, 2025)
Indonesia holds significant potential for sea cucumber aquaculture due to its abundant natural resources. This study aims to map suitable sites for sea cucumber farming around Saugi Island by analyzing physical and chemical water parameters using Geographic Information Systems (GIS). Data were collected from 10 sampling stations through field surveys and analyzed using the weighted overlay method in ArcGIS 10.8. Parameters evaluated included temperature, salinity, pH, dissolved oxygen, water clarity, and depth. Results indicate that the northern, southwestern, and eastern parts of Saugi Island are highly suitable for sea cucumber farming, while the northwestern, northeastern, and parts of the southeastern areas are less suitable. These findings provide a valuable reference for sustainable sea cucumber farming and can support local economic development.